Books or and Babies: Pregnancy and young parents in schools by Robert Morrell, Deevia Bhana & Tamara Shefer - Tracey Feltham-King (Perspectives in Education, 2015)
From text: From the outset, the title Books or and babies: Pregnancy and young parents in schools cleverly indicates the broad terms of reference for the investigation of the topic. The deliberate strikethrough of or being replaced by and frames the authors’ critical approach. In refusing to stay within the taken-for-granted binary where pregnancy and parenting are considered irreconcilable with schooling, the authors move the focus away from the individual young woman in order to pay long-overdue attention to the broader context in which pregnancy and parenting happens in South African schools.